DETECTION OF BACTERIA WITH POTENTIAL PATHOGENS IN PORCINE RESPIRATORY DISEASE COMPLEX - Suarjana, I Gusti Ketut; Besung, I Nengah Kerta; Pasek Gelgel, Ketut Tono; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2022)
This study aims to detect bacterial infectious agents in pigs with complex respiratory tract disease known as porcine respiratory disease complex (PRDC) in some pig herds in Bali and look for the right medication is use to handle the incidence. The research sample comes from Tabanan, Badung and Gianyar totaling 48 Samples were isolated and identified by methods: isolation, the primary test, biochemical test. Test of sensitivity to antibiotics using disc diffusion method according to Kirby-Bauer method. The result showed that bacterial agents isolated from pigs were among others Streptococcus spp. alfa hemolytic non-coagulase (41,6%), Staphylococcus spp. beta hemolytic noncoagulase (41,6%) and Escherichia coli. Staphylococcus spp. beta hemolytic non-coagulase and E. coli were sensitive to streptomycin, kanamycin, doxicyclin, clindamycin and bacitracin. To conclude, Streptococcus spp. alfa hemolytic non-coagulase were sensitive to streptomycin, kanamycin, clindamycin and bacitracin, but resisten to doxicyclin.